Systematic Literature Review: The Impact of Profitability, Leverage, and Taxation on Transfer Pricing in Companies - Santoso, Rizki Agung; Fuadah, Luk Luk (Balance : Jurnal Akuntansi dan Manajemen, 2025)
This study aims to analyze the impact of taxation, profitability, and leverage on transfer pricing using a Systematic Literature Review (SLR) approach. A total of 15 scholarly articles were analyzed to identify patterns of relationships between variables as well as research gaps in terms of country coverage, industry sector, theoretical frameworks, and variable measurement methods. The findings indicate that taxation has a significant and positive impact on transfer pricing, as companies facing higher tax rates tend to employ this strategy to allocate profits to lower-tax jurisdictions. Profitability also influences transfer pricing, although the results vary depending on the firm's structure and prevailing tax policies. Meanwhile, leverage is found to have a negative impact on transfer pricing, suggesting that highly leveraged firms exercise greater caution in engaging in transfer pricing to avoid additional tax risks. Beyond the primary factors, this study also identifies corporate governance, managerial bonus mechanisms, and macroeconomic conditions as moderating factors that can influence the relationship between taxation, profitability, and leverage on transfer pricing. The findings provide valuable insights for academics and practitioners in understanding how various factors shape transfer pricing decisions and highlight the importance of tax regulations in overseeing these practices.